Bowed Generation and Digital Ethics Challenges in Islamic Education - Yanti Yanti; Yulianto Nur Cahyono; Aida Hayani (Westscience Press, 2023)
Generation Bowing Down and the Challenges of Digital Ethics in Islamic Education